RANCANG BANGUN KEAMANAN PINTU BRANKAS MENGGUNAKAN RFID RC-522 DAN MODUL IoT WEMOS-D1-R1 - Hartanto, Sri; Nurdiantoro, Muhammad Rafli; Al Bahar, Abdul Kodir (JEIS: Jurnal Elektro dan Informatika Swadharma, 2026)
The high crime rate, especially theft, has prompted the development of a safe-deposit box equipped with intelligent monitoring technology to store valuable items, such as important documents, jewelry, and cash. The current safe-deposit box security system has the disadvantage of being easily accessed without permission, so a solution is needed to improve its security. This research aims to design and create a safe-deposit box door security system with an Internet of Things (IoT)-based RFID RC-522 module. This system can accurately identify users and monitor access in real time. The research method used is research and development, with a design for a safe-deposit box security system using the Arduino Wemos D1 R1 module as an Internet of Things (IoT) module, connected to the RFID RC-522 module, and programmed in the Arduino IDE to process input from the RFID RC-522 module. The results of the study show that the system works well, as indicated by the RFID RC522 module reading cards at an effective distance of approximately 2 cm. The LCDs show the RFID card reading status, and the Blynk application on a smartphone shows the same data as the safe-deposit box LCD